Pembaharuan Model Audit Akuntansi Dan Laporan Pertanggungjawaban Direksi Dalam Meningkatkan Kapasitas Produksi Pada PT.Bentoel Prima Malang - Ari Nurcahyo Darmawan,; Indah Datin Nadliroh, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2020)
This research examines the association of workload, auditor specialization, and audit committee as independent variables on audit quality. This research was conductedat manufacturing companies listed on PT.Bentoel Prima Malang. This research is important to do considering the literature review shows inconsistent results oneach research variable. The research sample was selected through purposive samplingmethod and using multiple regression as the basis of analysis. The results of the researchand hypothesis testing that have been carried out show that the first hypothesis is acceptedwhere there is a significant negative effect between workload and the quality of the auditresults. The second hypothesis is accepted where there is a significant positive effect ofauditor specialization on audit quality. The third hypothesis is rejected where there is nosignificant effect between audit rotation on the audit results. The fourth hypothesis isrejected, where there is no effect of the audit committee on the quality of the audit results.